Pestalotiopsis (Pestalotia) Diseases of Palm - Monica L. Elliott (EDIS)
The fungus Pestalotiopsis causes leaf spots, petiole/rachis blights and sometimes a bud rot of palms. In other words, unlike the other leaf spot and petiole blight pathogens, which attack either the leaf blade or the leaf petiole, Pestalotiopsis attacks all parts of the leaf from base to tip. It is also one of the more ubiquitous fungi in the palm canopy, and is easily isolated from healthy palm tissue. This document is PP-217, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date January 2006.